Development of a WiFi Smart Socket and Mobile Application for Energy Consumption Monitoring - Ungku Amirulddin U.A.; Ab Aziz N.F.; Baharuddin M.Z.; Nordin F.H.; Johari M.N.S. (Springer, 2023)
Energy efficiency; Energy utilization; IEEE Standards; Microcontrollers; Mobile computing; Wi-Fi; Wireless local area networks (WLAN); Energy consumption datum; Energy consumption monitoring; Internet of Things (IOT); Microcontroller unit; Mobile applications; Power factor measurements; Smart socket; User interaction; Internet of things